Frequency of occurrence of phonemes in Calicut and Eranakulam dialects of Malayalam - N, Sreedevi; M, Irfana (Journal of All India Institute of Speech and Hearing, 2013)
Malayalam is a Dravidian language primarily spoken in the southwest of India. The knowledge of the frequency of occurrence of phonemes in a language is essential to understand the language structure. This information is useful in the field of audiology and speech language pathology for preparation of assessment tools and treatment of communication disordered population. The present study aimed to compare the frequency of occurrence of various phonemes in Calicut and Eranakulam dialects of Malayalam using conversation samples. Participants were fluent native speakers of Calicut or Eranakulam dialects of Malayalam in the age range of 30 to 55 years. Fourteen conversation samples were recorded with seven groups from each dialect separately for 25-30 minutes. A minimum of 4 to 5 participants were present for each recording. The obtained samples were transcribed using both broad and narrow IPA transcription. Inter judge and intra judge reliability of phonetic transcription was calculated for 10% of the recorded samples. Recorded data was analyzed using the SALT software for obtaining frequency of phonemes. Mean and standard deviation of frequency of phonemes of all the fourteen samples were obtained. The analysis showed that /a/ was the most frequently occurring vowel and /k/ was the most frequently occurring consonant in both dialects. In Calicut dialect, the other most frequently occurring consonant in both dialects. In Calicut dialect, the other most frequently occuring vowels were /I, e, a: , e/ and consonants wer /n, t,t, l/.In Eranakulam dialect /a, I, e, a:/ were most frequently occurring vowels and consonants were /k, n,t, p, t, l, m/.The results obtained will help audiologists and speech language pathologists in developing and updating the existing test material for evaluating various communication disorders and also for selection of treatment targets in such population. The study also has implications in linguistics analysis, speech synthesis experiments and development of automatic speech recognition systems.